English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Implicitly differentiate 3x^2=(2-y)/(y+2)

help please!

2007-03-30 11:15:07 · 2 answers · asked by Nicky 2 in Science & Mathematics Mathematics

2 answers

3x^2 = (2 - y)/(y + 2)

All you have to keep in mind when doing implicit differentiation is that whenever you take the derivative of y, it is equal to dy/dx.

Differentiating, we get

6x = [ (dy/dx)(y + 2) - (2 - y)(dy/dx) ] / (y + 2)^2

To isolate dy/dx, multiply both sides by (y + 2)^2.

6x(y + 2)^2 = (dy/dx)(y + 2) - (2 - y)(dy/dx)

By symmetry,

(dy/dx)(y + 2) - (2 - y)(dy/dx) = 6x(y + 2)^2

Factor dy/dx,

[dy/dx] (y + 2 - (2 - y)) = 6x(y + 2)^2

[dy/dx] (y + 2 - 2 + y) = 6x(y + 2)^2

[dy/dx] (2y) = 6x(y + 2)^2

Divide both sides by 2y,

dy/dx = [ 6x(y + 2)^2 ] / [ 2y ]

dy/dx = [ 3x(y + 2)^2 ] / y

2007-03-30 23:00:55 · answer #1 · answered by Puggy 7 · 0 0

6x= 1/(y+2)^2 *[(y+2)(-y´)-(2-y)*y´)
6x= (-4y´)/(y+2)^2

2007-03-30 18:22:59 · answer #2 · answered by santmann2002 7 · 0 0

fedest.com, questions and answers